Levantamento de indicadores financeiros-chave da incorporação imobiliária - Amaral, Tatiana Gondim; Queiroz, Adriano Luiz Santos (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Real estate development is the business activity characterized by realty production that will include activities from the planning of a set of properties and their commercialization during construction. When we compare the indicators of this area with other types of companies, we realize that it is a subject still relatively little addressed in studies and, when studied, there are more references for Construction than for Real Estate Development. In this sense, a case study was conducted through semi-structured interviews with the purpose of raising the financial indicators, those that are most often taken into account at a strategic level (launch or continuation of a construction, reassess sales and competition), the degree of importance and the degree of difficulty in measuring these performance indicators. During the survey, it was found that the real estate developer analyzed has 60% of its indicators with the degree of importance five, the largest of the adopted scale, and has in its measurement degree the average measurement difficulty of 3.06. For market validation, seven of the eight common indicators with ADEMI-GO surveys have a degree of importance greater than four. The main difficulty in measuring the indicators raised is the excess of manual labor; in other words, the lack of integration between the Company's platforms that would compile the various input data into a summary, a single panel containing all indicators.